African independence how Africa shapes the world - Zuberi, Tukufu (Rowman & Litlefield, 2015)
African Independence is a dynamic discussion of how Africa shapes world events today. Tukufu Zuberi weaves interview excerpts and stories from many Africans he has met-from refugees to heads of state-with key events in African history to show the importance of understanding Africa today.